The Use of Military Imagery as an Exhortation for Ecclesial Unity in 1 Clement 37 and 2 Timothy 2:3–4 - Kim, Kangil (Religions, 2024)
The problem of schism is one of the major issues in 1 Clement. To resolve this problem, the author of 1 Clement exhorts the Corinthian believers to submit to their leaders by using military imagery. While the use of military imagery is often understood in reference to the author’s emphasis on peace and concord, what remains to be explored is the way in which the militaristic imagery in 1 Clement 37 can be read alongside 2 Timothy 2:3–4. Although there is no clear evidence of whether Clement draws on 2 Timothy or vice versa, I suggest that the militaristic imagery in 2 Timothy 2:3–4 offers a helpful analog for understanding the meaning of the use of military imagery in 1 Clement 37.